Validation of Bangla generalized anxiety disorder 7 scale among general population - Redwan, ASM; Karim, Md Rezaul; Royle, Ramendra Kumar Singha; Chowdhury, Ahmed Riad (Bangladesh Journal of Psychiatry, 2020)
Anxiety disorder is the most prevalent mental disorder in Bangladesh according to the estimation of World Health Organization (WHO). Among the anxiety disorders, generalized anxiety disorder (GAD) is most common and morbid one. The generalized anxiety disorder (GAD) 7 scale is widely used, highly sensitive and reliable scale to screen GAD and other anxiety disorder for both primary and clinical settings. Because of scarcity of properly validated Bangla version of GAD 7 screening tool among the general population, this study was aimed to develop such a version. This validation study was conducted in cross-sectional design from September, 2016 to August, 2018 in the department of psychiatry, Sylhet MAG Osmani Medical College Hospital, Sylhet. Adaptation was done as per Beaton et al., 2000 criteria. Total 61 patient aged e”18 years diagnosed as GAD by applying SCID CV and 65 age and sex matched healthy volunteer was taken as sample by purposively. Data was collected by administering written questioner with Bangla version of GAD 7 scale and Depression Anxiety Stress Scale (DASS) 21 Bangla. Convergent validity and discriminant validity was explored using DASS 21 Bangla scale. Data was analyzed using SPSS version 25. The result showed that, the Cronbach’s alpha value was excellent (0.90), test-retest and intra-class correlation was also good. Unidimensionality was confirmed, a cut-off point of 9 showed adequate value of sensitivity (85%) and specificity (80%) with area under curve being statistically significant (AUC=0.893-0.973). The scale showed good correlation with DASS 21 anxiety (0.637, p<0.001) and stress subscale (0.576, p<0.001). The metric properties of GAD 7 Bangla, its comparison with DASS 21 Bangla confirmed its cultural adaptation and validation. It would be helpful to identify the GAD in all age range of Bangla speaking people. Bang J Psychiatry 2020; 34(1):3-8